Perbandingan Laju Korosi Baja Mild Steel yang Dilapisi Galvanis dan Cat pada Limbah Sawit - Muhammad Aidil Fitra Izmail; Fatahul Arifin; Syamsul Rizal (Politeknik Negeri Lhokseumawe, 2026)
This study aims to quantitatively compare the corrosion rate of mild steel coated with galvanizing, black spray paint, silver spray paint, and white spray paint when exposed to palm oil mill effluent. The experiment was conducted using the weight loss method in accordance with ASTM G31 standards. Mild steel specimens with dimensions of 150 mm × 25 mm × 2 mm were prepared, coated, and immersed in 4 L of conditioned palm oil wastewater for 22 days. Environmental parameters, including pH (4.5–5.2) and temperature (28–34°C), were continuously monitored throughout the testing period. Each test was performed in triplicate to ensure data reliability. The results indicate that coating type has a significant effect on corrosion resistance. Galvanized specimens exhibited the best performance, with a corrosion rate approaching 0 mm/year and a mass loss of ≤1%. In contrast, black spray-coated specimens showed the highest corrosion rate of 0.77 mm/year and mass loss exceeding 1.8%, followed by silver and white coatings, each with a corrosion rate of 0.26 mm/year. The superior performance of galvanizing is attributed to its sacrificial protection mechanism and the formation of stable passive layers such as ZnO and ZnCO₃, which effectively inhibit corrosion processes. In conclusion, galvanizing is the most effective coating method for protecting mild steel in aggressive environments such as palm oil mill effluent.